Estudio comparado y sociojurídico de la unión de hecho desde el caso ecuatoriano con los países de América Latina y/o la Unión Europea - Muñoz Vinueza, Raúl Eduardo (2018)
Resumen:The development of societies in the world has been very quick, especially during the twentieth century, where the rise of science, industry and technology have allowed the inhabitants of the planet to make a great qualitative leap in the way they live their lives. However, social relations have not advanced at the same pace, as industry, science and technology. In this context, societies in the world began to "convulse" demanding new rules for social relations through social movements, mainly young people and marginalized groups people from the 1950 s of the twentieth century, who demonstrated their dissatisfaction by rebelling against the normal (preconceived) way of life. This social revolution of the young people and marginalized groups gave way to the breaking of traditional schemes regarding freedom, the relationships of the children with the parents, traditional education and ways of expressing themselves mainly with respect to the conception of family, At that time, couples who began to live together in fact unions "as in a marriage" emerged openly and frontally, but outside the law.